2019
DOI: 10.2196/12793
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting to a Randomized Controlled Trial of a Web-Based Program for People With Type 2 Diabetes and Depression: Lessons Learned at the Intersection of e-Mental Health and Primary Care

Abstract: Background E-mental health (eMH) interventions are now widely available and they have the potential to revolutionize the way that health care is delivered. As most health care is currently delivered by primary care, there is enormous potential for eMH interventions to support, or in some cases substitute, services currently delivered face to face in the community setting. However, randomized trials of eMH interventions have tended to recruit participants using online recruitment methods. Consequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…First, our study showed that social media is a very effective recruitment channel in Lebanon. This finding is congruent with other studies ( Carmi and Zohar, 2014 ; Fletcher et al, 2019 ; Kayrouz et al, 2016 ; Ünlü Ince et al, 2014 ). Yet, the recruitment strategy needs further refinement to improve recruitment of Syrians, as the numbers recruited through social media were much lower (24% of participants were Syrians).…”
Section: Discussionsupporting
confidence: 93%
“…First, our study showed that social media is a very effective recruitment channel in Lebanon. This finding is congruent with other studies ( Carmi and Zohar, 2014 ; Fletcher et al, 2019 ; Kayrouz et al, 2016 ; Ünlü Ince et al, 2014 ). Yet, the recruitment strategy needs further refinement to improve recruitment of Syrians, as the numbers recruited through social media were much lower (24% of participants were Syrians).…”
Section: Discussionsupporting
confidence: 93%
“…The uptake of web-based mental health programs within primary care (eg, via general practitioners [GPs]) is emerging but has been relatively slow [ 35 - 37 ]. Previous research conducted in Australia [ 38 ] examined the potential of recruiting people with type 2 diabetes and depression into a web-based mental health program. This study found that recruitment through general practice (n=24 participants) was unsuccessful compared with going through registries and word of mouth (n=196) or web-based recruitment methods (eg, Facebook; n=520) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted in Australia [ 38 ] examined the potential of recruiting people with type 2 diabetes and depression into a web-based mental health program. This study found that recruitment through general practice (n=24 participants) was unsuccessful compared with going through registries and word of mouth (n=196) or web-based recruitment methods (eg, Facebook; n=520) [ 38 ]. The authors identified staff attitudes toward internet interventions as a key barrier to recruitment through primary care in Australia [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Full details of recruitment for the SpringboarD trial are detailed in separate papers [21,23]. In summary, recruitment began in September 2015 and continued until November 2017.…”
Section: Participants and Settingmentioning
confidence: 99%
“…As a result, near-normal scores on baseline variables weakened tests of efficacy, and our results are largely indicative of people with T2DM and mild distress or impairment. Nonetheless, the inclusion of multiple follow-up assessments in this analyses and large sample that our study comprised afforded us the opportunity to extend the trial findings by analyzing recruitment strategies [23] and examining study attrition in both short and long terms.…”
Section: Strengths and Limitationsmentioning
confidence: 99%